Relapses of traumatic peroneal tendons subluxation already treated surgically: a new surgical approach - Alessandro Tomarchio; Luigi Meccariello; Dariush Ghargozloo; Andrea Pasquino; Enrico Leonardi (Medicinski glasnik, 2021)
Aim: To illustrate the surgical treatment of relapses of traumatic peroneal tendons subluxation. Methods: We came across a young woman, who sustained a sprain in her dominant ankle after a trauma; we noticed subluxation of the peroneal tendons during eversion and extension of the foot. She referred to a previous accident some years before with peroneal tendon subluxation treated by superior peroneal retinaculum (SPR) sutures with a synthetic braided absorbable material. We prescribed conventional radiography, magnetic resonance imaging (MRI) and performed surgery: we removed scar tissue, reattached the retinaculum using suture anchors strengthening it with an acellular dermal matrix allograft patch. Results: Periodic clinical follow-ups until 24 months were performed evaluating the stability of the ankle, checking the range of movement, and the Visual Analogic Scale (VAS) and American Orthopedic Foot and Ankle Society Score (AOFAS) was administered. At the first check the subluxation was resolved and the ankle was stable. The VAS scale had the value of 0 at the 3-month follow-up maintained until the final check. Conclusion: Relapsing traumatic peroneal tendons subluxation is rare, as well as the possibility of a re-intervention years later. This technique seems to guarantee an excellent result even in the long term, allowing resolution of pain and joint stability. In fact, the use of acellular dermal patch is an already commonly described technique for the augmentation in rotator cuff and hip capsular repair; no reports are available in literature in relation to the use of graft for the repair of the superior peroneal retinaculum.
Keywords: ankle sprains; allografts; suture anchors; suture techniques; tendon injuries